Geometric illustrations of the conjugacy principle - M. L. Martins, Fernando; Vicente, M. A. Facas (Instituto Politécnico de Coimbra, Escola Superior de Educação de Coimbra, 2009)
In this paper, we illustrate the use of the conjugacy principle in several geometric transformations: translations, reflections and rotations. Our context are the real spaces R2 and R3. The main role is played by matrices, as it is to be expected. The referred to transformations are fundamental when studying motion questions in the Mechanics, Computer Graphics, Robotics, Computer Games, etc.. Our didactical goals are focused on the acquisition and development of spatial abilities, in order to get a better perception, interpretation and forecasting of the geometrical transformations in our physical world.
Keywords: Didactics of mathematics; Geometry; Conjugacy principle; Translation; Reflection; Didáctica da matemática; Geometria; Princípio da conjugação; Translação; Reflexão; Rotação